IKLAN RADIO YANG PEDULI KESETARAAN GENDER DI KOTA JAYAPURA PROVINSI PAPUA - Sitorus, Ferry Rhendra Pananda Putra (Kafa`ah: Journal of Gender Studies, 2023)
During the pandemic period, access to radio media is a good choice. By accessing various broadcast programs on the radio, radio listeners can use the health procedure by keeping a distance and avoiding crowds with many numbers of people. Through radio broadcasts, information and entertainment can be obtained through broadcast or advertising programs. The process of gender socialization can be carried out through advertisements on the radio for listeners, which can also affect the listener's environment. There are a number of examples of advertisements that do not support gender equality. Efforts to find examples of advertisements that support gender equality formulate the problem in this study. The research was carried out on Radio Swaranusa Bahagia and Radio Bahana Sangkakala in Jayapura City. There are eleven advertisements highlighted as sources of information besides literary techniques and observations. There are a number of advertisements supporting gender equality. Among them are equal access and opportunity to buy computers, computer credit, worship, get information, and care for health related to the prevention of COVID-19. It is hoped that by knowing this advertisement that supports gender equality, listeners can understand gender equality and apply it appropriately to their family, social, and work environments. By producing the results of research on radio advertisements that support gender equality, further research can be developed in the future. Future research related to radio advertising that supports gender equality can also be carried out on television and print media in Jayapura City, Papua Province.Pada masa pandemi akses pada media radio menjadi pilihan yang tepat. Dengan mengakses berbagai program siaran pada radio, dapat dilakukan protokol kesehatan melalui menjaga jarak dan menghindari kerumunan dengan banyak orang. Melalui siaran radio dapat didapatkan informasi dan hiburan melalui program siaran ataupun iklan. Proses sosialisasi gender dapat dilakukan melalui iklan pada radio kepada para pendengarnya yang juga dapat mempengaruhi lingkungan terdekat pendengar tersebut. Terdapat sejumlah contoh iklan-iklan yang tidak mendukung kesetaraan gender. Upaya untuk mengetahui contoh iklan yang mendukung kesetaraan gender yang menjadi rumusan masalah dalam penelitian ini. Lokasi penelitian dilakukan pada Radio Swarannusa Bahagia dan Radio Bahana Sangkakala di Kota Jayapura. Terdapat sebelas iklan yang disoroti sebagai sumber informasi selain teknik literatur dan observasi. Terdapat sejumlah iklan yang mendukung kesetaraan gender. Diantaranya adalah kesamaan akses dan kesempatan dalam membeli komputer, kredit komputer, beribadah, mendapatkan informasi dan peduli kesehatan terkait pencegahan Covid-19. Diharapkan dengan mengetahui iklan yang mendukung kesetaraan gender ini para pendengar dapat memahami kesetaraan gender dan menerapkan secara tepat pada lingkungan keluarga, pergaulan dan pekerjaannya. Dengan dihasilkannya hasil penelitian mengenai iklan di radio yang mendukung kesetaraan gender maka dapat dikembangkan penelitian lanjutan pada waktu mendatang. Penelitian mendatang terkait iklan di radio yang mendukung kesetaraan gender tersebut dapat dilakukan juga pada media televisi dan cetak di Kota Jayapura Provinsi Papua